Optimizing the Use of Technology in Business Management in the Digital Era - Putri Mauliza; Muhammad Ras Muis; Fahmi Armanda (Outline Journal of Community Development, 2023)
In the digital era, technology has become a major driver of transformation in business management. Optimizing the use of technology allows business actors to improve operational efficiency, expand market reach, and strengthen competitiveness. This article discusses the results of training and implementation of technology in business management, focusing on the benefits, challenges, and recommendations for the sustainability of digital transformation. The training results show that the use of management software, digital media, and analytical technology can increase productivity, reduce costs, and improve customer relationships. However, several challenges such as limited infrastructure, low digital literacy, and resistance to change are still obstacles. To overcome these challenges, continuing education, infrastructure improvement, and financial support are important steps. By optimally utilizing technology, business actors can create innovation, increase efficiency, and adapt to rapid market changes. This article emphasizes the importance of collaboration between the government, private sector, and business actors to accelerate business digitalization, thereby creating a more competitive and sustainable ecosystem. Optimizing technology not only has an impact on the growth of individual businesses, but also makes a major contribution to the growth of the national economy as a whole.